If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = 3x + 1 Reorder the terms: 5 + -1x = 1 + 3x Solving 5 + -1x = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + -1x + -3x = 1 + 3x + -3x Combine like terms: -1x + -3x = -4x 5 + -4x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -4x = 1 + 0 5 + -4x = 1 Add '-5' to each side of the equation. 5 + -5 + -4x = 1 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 1 + -5 -4x = 1 + -5 Combine like terms: 1 + -5 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 11x^2+9x+5=0 | | X+8X-9=0 | | -7x+8+9x-11-13x= | | 5x+2=7x+10 | | 245-t=0 | | 4(x+2)-1=6x-2(-1+x) | | 3(x-18)=9x | | 25y^2-34y+9=0 | | 84*5= | | 5x-6=5(x-1) | | 4x^2-53x-105=0 | | 8p-2q=2p-4q | | (x-y)(x^2+13xy+y^2)=0 | | (x+5)+4=16 | | 16x+8=11+15x | | x^2-27x+23=0 | | -x+7=-24 | | (2x+2)2=16 | | 25-16v^2=12v(v+5) | | 7(x+3)-9(x+1)= | | 4x^2-53-105=0 | | 4x-7=-4+5x | | 3w+2+w=36 | | 5+2.3x=3-.5y | | -3(v+w)-6(-4w+v)= | | -2v-3v=17+4 | | 4r-5t+9=5t-9 | | 3(5y-4)-2y=27 | | k+8=14 | | x-47=100 | | -36-6a=-6(3a+2) | | 2x-15=-y |